2020
DOI: 10.5603/fhc.a2020.0023
|View full text |Cite
|
Sign up to set email alerts
|

An overview of applications of CRISPR-Cas technologies in biomedical engineering

Abstract: Clustered Regulatory Interspaced Short Palindromic Repeats (CRISPR) is one of the major genome editing systems and allows changing DNA levels of an organism. Among several CRISPR categories, the CRISPR-Cas9 system has shown a remarkable progression rate over its lifetime. Recently, other tools including CRISPR-Cas12 and CRISPR-Cas13 have been introduced. CRISPR-Cas9 system has played a key role in the industrial cell factory's production and improved our understanding of genome function. Additionally, this sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…Initial studies in bacterial cell lines [98,99] and mammalian cells [100][101][102][103][104] have shown that the biologically engineered CRISPR-Cas technology has future potential for correcting gene mutations. Such as malaria blocking genes in mosquitoes [105][106][107][108][109][110], genome editing in zebrafish [111][112][113], removing HIV genes [64,[114][115][116], hepatitis C virus [117] or Parkinson's disease [118]. However, this exciting progress may have unintended consequences and impacts due to 'off-target' effects, which recently are the main limitations of the CRISPR-Cas system because applied genetic corrections can have unpredictable results for future generations.…”
Section: The Immunization and Interference In Prokaryotic Cellsmentioning
confidence: 99%
“…Initial studies in bacterial cell lines [98,99] and mammalian cells [100][101][102][103][104] have shown that the biologically engineered CRISPR-Cas technology has future potential for correcting gene mutations. Such as malaria blocking genes in mosquitoes [105][106][107][108][109][110], genome editing in zebrafish [111][112][113], removing HIV genes [64,[114][115][116], hepatitis C virus [117] or Parkinson's disease [118]. However, this exciting progress may have unintended consequences and impacts due to 'off-target' effects, which recently are the main limitations of the CRISPR-Cas system because applied genetic corrections can have unpredictable results for future generations.…”
Section: The Immunization and Interference In Prokaryotic Cellsmentioning
confidence: 99%
“…An RNA-designed (single guide RNA [sgRNA]) for the target point is responsible for endonuclease protein (Cas9[CRISPR-associated protein 9]), Cas12, and Cas13 guidance. By use of the CRISPR toolkit and modified CRISPR toolkit systems, we can knock-in and knock-out genes, transcription activation, and suppression, epigenetic changes, edit the base, and image-specific nucleic acids ( Adli, 2018 ; Jamehdor et al, 2020 ). Research studies have shown that this system is effective in RNA and DNA editing ( Kushawah et al, 2020 ; Ran et al, 2013 ).…”
Section: Main Textmentioning
confidence: 99%
“…Some different stem cell types have so far been successfully used in clinical studies and have received scientific approval. Besides viral genome modification, more and more publications are confirming that CRISPR/Cas9 genome editing is a potent technique that can greatly advance biomedicine, such as in virus genome editing and in stem cell research [ 11 , 17 , 18 , 19 ]. Organoids are interesting new systems that help us improve our knowledge of diseases’ mechanisms, development, evolution, homeostasis, and therapy.…”
Section: Introductionmentioning
confidence: 99%